Pengaruh metode pembersihan kombinasi terhadap kekasaran Basis gigi tiruan akrilik - Rukmana, Livia; Adrian, Nova (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Background: Tooth loss is a problem often occurs in old age, so tooth replacement may be needed. The most commonly used base material is hot polymerization acrylic resin. The cleanliness of dentures is very important. The method used is a combination method, which are mechanical methods and chemical methods using sodium perborate in general. Cleaning dentures can affect the surface roughness of the base. Objective: To find out whether there is an effect of a combination cleansing method on the surface roughness of a complete acrylic denture base. Method: 20 samples of 20x10x3 mm of hot polymerization acrylic resin were prepared and soaked in a solution of effervescent polydent (sodium perborate) tablets for 8 hours. After that, brushing is carried out on the sample for 90 seconds before the sample is soaked again using tap water. This treatment was repeated for 30 days. Results: The combination cleansing method uses a solution of effervescent polident tablets (sodium Perborate) and the brushing of the sample results in significant changes in surface roughness (p <0.05). Conclusion: The combination cleansing of brushing and soaking using effervescent (polydent) tablets containing alkaline peroxide affects the roughness of the acrylic resin denture base, thus allowing increased retention of microorganisms